Investigation of flexural mechanical and creep properties of sleeve reinforced pultruded glass fibre reinforced polymer composite for crossarm application - Namasivayam Sukumaar, Vijayvignesh; Ishak, Mohamad Ridzwan; Abdullah, Mohd Na’Im; Mohd Zuhri, Mohamed Yusoff; Muhammad Rizal, Muhammad Asyraf (Nature Research, 2025)
Pultruded glass fiber-reinforced polymer (PGFRP) composites are innovative materials used in high-rise transmission towers that undergo failure due to long-term static loading phenomenon. This research focuses on retrofitting PGFRP composite cross-arms with plug-in type sleeve reinforcements by employing a three-point bending (3 PB) test to analyze the cross-arm’s elastic properties, flexural creep response, and deflection behaviour. The addition of the sleeve retrofit significantly improved the load–deflection behaviour and long-term creep resistance, by 45.30% and 47.10%, respectively. Findley’s power law model was used to accurately predict the viscoelastic response of the structure, revealing that the virgin cross-arm experienced a 75% drop in elastic modulus, while the sleeve-reinforced cross-arm saw only a 34% decrease indicating over 40% improvement in the cross-arm’s ability to resist deformation over extended periods. Additionally, the overall reduction factor improved by 0.51 in contrast to virgin cross-arm. The sleeve-reinforced cross-arm showed reduced deflection, better creep resistance, increased bending strength, and a longer theoretical lifespan. Predictions indicate that the improved cross-arm surpasses the current one in long-term mechanical performance.